Respuesta :
we are asked to solve for v in the expression u = vw + z. In this case, the first step is to subtract both sides by z first then divide the whole equation by w. The final result or expression is equal to v = (u-z) / w. Since nothing can be cancelled, this is the simplest and final expression
Answer:
The value of the equation for v is [tex]v=\frac{u-z}{w}[/tex].
Step-by-step explanation:
Consider the provided equation.
[tex] u=vw +z[/tex]
We need to solve the equation for v.
Subtract z from both sides.
[tex] u-z=vw +z-z[/tex]
[tex] u-z=vw [/tex]
Divide both the sides by w.
[tex]\frac{u-z}{w}=\frac{vw}{w} [/tex]
[tex]v=\frac{u-z}{w}[/tex]
Hence, the value of the equation for v is [tex]v=\frac{u-z}{w}[/tex].